Redundant and safe work implementation for S7-1200 PLC family - Konuk, Okan (Institute of Science and Technology, 2020)
One of the most important components of the automation field, which has an undeniable importance in today's technology, is undoubtedly seen as Programmable Logical Controllers (PLC). These devices are found in almost every area of industrial applications and are usually at the center of control and automation systems. Before these devices were discovered, industrial control systems needed relay and contactor based technology. However, the fact that the relays and contactors are not long-lived, are very easily affected by the industrial environmental conditions, and most importantly, the lack of a modular structure led to the debut of PLCs with the developing industry. This process, which started in the late 1960s, has improved day by day and has taken its current form. As the operating principle, a PLC is a microprocessor based device that processes the data it receives from the input elements to the output elements according to the program written in it. Input elements are generally composed of units such as sensors, switches and buttons, while output elements are usually units such as leds, drivers and motors. A PLC can also be defined as an electronic system with sections such as input/output units, memory and central operating unit (CPU). Many basic logical operations such as timing, counting and sequencing are performed by these devices. On the other hand, these devices can be used in many functions such as motion control, process control and data control. With the developing technology and industry, new requirements have forced these devices to develop continuously. The advancement of communication, processor power and memory management each period has enabled the development of new PLCs to be more compact, faster, smaller and also have more memory. The process that started from the debut of PLCs brought important changes for machine manufacturers. The way the machines are connected to each other has been changed and as a result, PLCs have replaced the classical relays. However, these regulations caused PLCs to stay away from machine safety. For this reason, certain standards have been introduced for systems where safety is critical and potential consequences can harm both the environment and human life.
S7-1200 plc ailesi için yedekli ve emniyetli çalışma uygulaması
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: Components of Petri Nets; Petri net state machine; PLC models